STRATEGI PROMOSI DINAS KEBUDAYAAN DAN PARIWISATA DALAM MEMPERKENALKAN WISATA BERSEJARAH RUMAH SINGGAH TUAN KADI DI KOTA PEKANBARU - Saputra, Erik; Awza, Rusmadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Rumah Singgah Tuan Kadi is one of the historical tourist objects in Pekanbaru City. Located in Badar village, Senapelan sub-district, Rumah Singgah Tuan Kadi is a strategic tourist attraction because it is located on the banks of the Siak river, Pekanbaru City and has also been made a cultural heritage certified by the Pekanbaru City Culture and Tourism Office. However, there are still many people in Pekanbaru who do not know about the existence of Rumah Singgah Tuan Kadi. Therefore, researchers are interested in conducting research on how the "Promotion Strategy of the Culture and Tourism Office in Introducing Historical Tourism Rumah Singgah Tuan Kadi in Pekanbaru City with the aim of knowing how social media marketing, sales promotion, and events are being conducted.